Earnings and Cash Flow Information on Its Value Relevance by The Book Value - Bawono, Andy Dwi Bayu; Ramadhanti, Mila; Kurniawati, Lintang (Universitas Muhammadiyah Surakarta, 2020)
This study aims to examine the relationship of earnings and operating cash flow as an independent variable on the value relevance of accounting information proxied by stock returns by using book value as a moderating variable. The utilitation of stock returns as an independent variable is choosed as previous research on value relevance tends to use stock prices as an independent variable. The sample of this study is all population of companies listed on the Jakarta Islamic Index (JII) in the 2016-2018 period June-November (issued from June 1st) using saturation sampling. The data used in this study is compound from annual reports in the Indonesia Stock Exchange (IDX) and stock prices from Yahoo Finance. Further, data were tested using multiple linear regression analysis. The results showed that earnings and cash flow have an effect on value relevance proxied by stock returns. However, book value neither strengthens nor weakens earnings and cash flow towards stock returns as a moderating variable.Â Keywords : Earnings, Operation Cash Flow, Stock Return, Value Relevance, Jakarta Islamic Index